1994
DOI: 10.1161/01.cir.90.3.1129
|View full text |Cite
|
Sign up to set email alerts
|

Three peptides from the atrial natriuretic factor prohormone amino terminus lower blood pressure and produce diuresis, natriuresis, and/or kaliuresis in humans.

Abstract: ProANFs 1-30, 31-67, and 79-98, as well as ANF have significant blood pressure-lowering and diuretic properties. ProANFs 1-30 and 31-67 also have natriuretic properties in humans that are significantly (P < .001) prolonged compared with ANF. ProANF 79-98, although not possessing any natriuretic property, is the strongest stimulator of potassium excretion of the four atrial natriuretic peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
171
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(180 citation statements)
references
References 18 publications
5
171
1
3
Order By: Relevance
“…Within this 126-a.a. prohormone are several peptide hormones with blood pressure lowering, natriuretic, diuretic, and/or kaliuretic (i.e., potassium excreting) properties in both animals (20,21) and humans (22,23). These peptide hormones, numbered by their a.a. sequences beginning at the N-terminal end of the ANP prohormone, consist of the first 30 a.a. of the prohormone (i.e., long-acting natriuretic hormone;…”
Section: Gene Products Of the Proanp Genementioning
confidence: 99%
“…Within this 126-a.a. prohormone are several peptide hormones with blood pressure lowering, natriuretic, diuretic, and/or kaliuretic (i.e., potassium excreting) properties in both animals (20,21) and humans (22,23). These peptide hormones, numbered by their a.a. sequences beginning at the N-terminal end of the ANP prohormone, consist of the first 30 a.a. of the prohormone (i.e., long-acting natriuretic hormone;…”
Section: Gene Products Of the Proanp Genementioning
confidence: 99%
“…A signal peptide on the N-terminus of the pre-prohormone is cleaved from the pre-prohormone in the endoplasmic reticulum resulting in a 126 amino acid prohormone, which is the storage form of four hormones from this prohormone and they are the major constituents of the atrial granules found in the heart (24-26). The ANP prohormone is cleaved into four peptide hormones upon release from the heart (28,29). These four peptide hormones consist of the first 30 amino acids of the prohormone's N-terminal end (i.e.…”
Section: To 88% By These Peptides But They Do Not Affect Stat1 Therementioning
confidence: 99%
“…These four peptide hormones consist of the first 30 amino acids of the prohormone's N-terminal end (i.e. amino acids 1-30) named long-acting natriuretic peptide (LANP), amino acids 31-67 of the ANP prohormone produce vessel dilator, amino acids 79-98 produce kaliuretic peptide and amino acids 99-126 produce ANP (27,28). These peptides were named for their most potent known biological effects at the time of naming (28).…”
Section: To 88% By These Peptides But They Do Not Affect Stat1 Therementioning
confidence: 99%
See 2 more Smart Citations